Pengabdian Masyarakat: Peningkatan Pengetahuan Dan Keterampilan Kader Kesehatan Dalam Pelayanan Keperawatan Dasar - Nur Ambiya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Health cadres are a crucial element in the community-based health care system because they act as a liaison between health workers and the community. However, limited knowledge and skills of cadres in basic nursing services remain a common problem in the field. This community service activity aims to improve the knowledge and skills of health cadres in basic nursing services through structured education and training. The methods used include counseling, interactive discussions, demonstrations, and hands-on practice. Evaluation was conducted through observation and post-activity discussions. The results of the activity indicate an increase in cadres' understanding of basic nursing concepts and improved skills in performing simple nursing procedures. This activity is expected to improve the quality of health services in the community and support promotive and preventive efforts.